(untitled) (Herald of Journalism, 2017)
The proposed article examines the role of the mass media as an organization having an effect on the formation of public opinion. Nowadays mass media really became the most effective manipulator of public opinion and, unfortunately, is very rarely in the public interest. In this regard, the main issue ofthe scientific article is to determine the influence of the media on the formation of public opinion at the present stage. This research evaluates the role of the media in formation public opinion. The author in the article shows the features of the creative work of the journalist and the realization of professional special interests in the status of the journalist, which derived from the specificity of its social role . The article also discusses the most important properties that together distinguish journalism from other professions, and above all about its artistic character and the public service elements. The article also provides an overview on the recently published study about the journalism and public opinion on the media system.